An atypical presentation of high potassium renal secretion rate in a patient with thyrotoxic periodic paralysis: a case report - Mei-Lan Tu; Yu-Wei Fang; Jyh-Gang Leu; Ming-Hsien Tsai (BMC Nephrology, 2018)
Abstract Background Hypokalemia is one of the most common clinical electrolyte imbalance problems, and thyrotoxic periodic paralysis (TPP) is a leading cause of presentation to the emergency department. Low renal potassium secretion rates, a normal acid–base balance in the blood, and hyperthyroidism are the hallmarks of suspected TPP. Case presentation Here we report the case of a 36-year-old man who presented to the emergency department with a sudden onset of acute muscle weakness at 5 h prior to admission. Biochemistry tests revealed hypokalemia with hyperthyroidism and renal potassium wasting. TPP was initially not favored due to the presence of renal potassium wasting. However, his serum potassium level rebounded rapidly within several hours after potassium supplementation, indicating that the intracellular shifting of potassium ions was the main etiology for his hypokalemia. The early stage of TPP development may have contributed to this paradox. Conclusion Therefore, it is premature to rule out TPP based on the presentation of high renal potassium secretion rates alone. This finding may result in an incorrect impression being made in the early stage of TTP and may consequently lead to an inappropriate potassium supplementation policy.